Floral larceny by the stingless bee Trigona amalthea on granadilla (Passiflora ligularis Juss) - Gutiérrez-Chacón, Catalina; Pantoja-Santacruz, Johanna; Klein, Alexandra Maria (Journal of Pollination Ecology, 2018)
Floral larceny (robbery and thievery of nectar and/or pollen) by some species of stingless bees in the genus Trigona has been long reported for several plant species, although the consequences for plant reproduction are unknown for many cultivated species. Here we i) describe the behavior of Trigona amalthea Olivier in relation to flowers of granadilla (Passiflora ligularis Juss), ii) provide a preliminary assessment of fruit set in six experimental plots, one exposed to attacks by T. amalthea only (infested) and the other plots without attacks from any species (control plots), and iii) discuss potential strategies for preventing damage from T. amalthea based on species traits such as foraging range. We observed T. amalthea chewing styles and stigmas of both flower buds and mature flowers while primarily extracting pollen. Destruction of floral structures prior to ovule fertilization probably accounts for the significant reduction in fruit set in the infested plot compared to control plots, although replicated infested plots are required for robust confirmation. Moreover, negative effects may be intensified by the small size of the experimental plot. Further studies are needed to assess impacts on commercial plantations, including investigations into a potential dilution effect in larger crop fields, as well as plant mechanisms to cope with consumer damage (resistance and tolerance). Legitimate pollinators were found to cover larger distances than T. amalthea. Therefore, locating crop fields at optimal distances from bee nesting habitat might reduce damage by balancing bee services and disservices.